The Unknown War - WWII and the Epic Battles of the Russian Front Episode 1-20 - Karmen, Roman; Lancaster, Burt (Shout Factory, 2011)
The greatest battles of World War II and the most devastating human losses which the modern world has ever seen occurred on Russian soil during 1941-45, on a battlefield that is unknown to most Americans: the conflict between Hitler's Germany and Stalin's Russia. "The Unknown War: World War II and the Epic Battles of the Russian Front" is a landmark television series written by Rod McKuen that captures both the gripping detail and the epic sweep of Hitler's brutal invasion. Hosted by Academy Award winner Burt Lancaster, the sprawling 20-part series features previously unseen footage (shot by Soviet camera crews on the frontlines of the war) from deep within the Kremlin vaults. The series was pulled from public television prematurely due to viewer complaints following the Soviet invasion of Afghanistan. The remaining episodes have never been seen, making the show legendary in WWII history circles and inspiring a number of smaller-scale knock-offs over the past three decades. Now, war-history buffs young and old can finally witness "The Unknown War" for themselves in this long-awaited [www.shoutfactory.com]
Keywords: DVD-Video